International standards for statistics on the government sector - Valentová Půlpánová, Lenka; Hronová, Stanislava, 1954-; Hindls, Richard, 1950-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2011)
The analysis of the government sector gained prominence after the World War II as the Keynesian theory attributed the government sector key importance in battling economic cycle and the post-war reconstruction and development involved state interventions on a large scale. In 1990s a strength-ened interest in the government sector was triggered by the need to coordinate fiscal policies and closely monitor fiscal health in the countries forming the Economic and Monetary Union. Finally, in the context of the recent global economic crisis, the government sector returned to the centre of the economic policy debate as fiscal policy was used as a main tool to fight the economic recession and subsequently sustainability of government finances became a pressing issue for many countries around the Globe. Increasing importance of the fiscal analysis and fiscal policymaking always generated and continues to generate demand for appropriate statistical data. The international statistical standards played a key role in meeting these requirements. This dissertation offers a comprehensive historical overview, a comparative analysis and evaluation of main internationally recognised statistical standards dealing with the government sector produced by the United Nations, the OECD, the European Communities (Eurostat), the IMF and the European Central Bank. It covers a period since the first international guidelines in late 1940s up to present. It analyses evolution of the statistical treatment of the government sector including its historical roots and gradual revisions and extensions to reflect changing needs and shifts in economic environment.
The study compares individual standards with each other and across time and points out differences in basic definitions, concepts and classifications, the institutional coverage of the government sector, structure of government accounts and balancing items, integration of flow accounts with balance sheets and consolidation of transactions or stocks. The dissertation shows that the international statistical standards were successful in offering common statistical guidance, recommendations and best practices. The international organizations have proven to be well suited to deliver widely acknowledged standards. Their cooperation with national statistical agencies and engagement of the most competent experts in the field contributed to building credibility of these statistical systems, if properly applied. The comparative analysis also demonstrates a clear long-term effort of the international statistical community to enhance international harmonization. The application of the international statistical standards also improved quality and availability of government statistics as individual countries are in principle bound -- through their memberships in the international organizations -- to compile agreed data on the basis of a common methodology. This was in particular the case for EU countries for which provision of statistical data according to a given standard is legally binding, as the data are relevant for budgetary and surveillance procedures. As a special case, the history since early 1990s and current situation of statistics on the government sector in the Czech Republic is presented.
Vedoucí práce: Stanislava Hronová
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: statistika [obor disert. práce]; disertace; dissertations